Late observation of the neuroprotective effect of citicoline in uveitis: an impact on the ultrastructure of the choriocapillaris, retina and optic nerve in rabbits - Ульянов, Вадим Олексійович; Ульянов, В. О.; Ulianov, Vadym O.; Горянова, Ільїна Сергіївна; Горянова, І. С.; Horianova, Ilina S.; Молчанюк, Наталія Іванівна; Молчанюк, Н. І.; Molchaniuk, Nataliia I. (Odesa : SI «The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine», 2024)
Purpose: To evaluate the ultrastructure of the choriocapillaris, retina and optic nerve (ON) in citicoline-treated versus non-treated rabbits at the late time point after inducing non-infectious anterior and intermediate uveitis. Methods: The ultrastructure of the rabbit choriocapillaris, retina and ON was evaluated at day 55 after the initiation of uveitis. Results: Experimentally induced uveitis caused neurodegenerative changes in the retina and ON. Neuroprotective treatment activated intracellular compensative processes resulted in reduced signs of hydropic degeneration and normalized cell ultrastructure, and contributed to the activation of metabolism in ON glial cells and axoplasm. Conclusion: Neuroprotective treatment for non-infectious anterior and intermediate uveitis resulted in a reduction in neurodegenerative changes in the retina and ON. Мета. Дослідити ультраструктуру хоріокапілярів, сітківки і ЗН ока кролів в пізні строки після моделювання неінфекційного переднього і середнього увеїту без та з лікуванням нейропротектором цитіколіном. Матеріал та методи. Вивчалась ультраструктура хоріокапілярів (ХК), сітківки та ЗН кролів на 55-у добу після введення провокуючої дози. Результати. Модельований з увеїт викликав нейродегенеративні зміни в сітчастій оболонці та зоровому нерві. Застосування нейропротектора активувало внутрішньоклітинні компенсаторні процеси, що призводили до зменшення ознак гідропічної дегенерації та нормалізації ультраструктури клітин, а також сприяло активації метаболічних процесів в гліальних клітинах і аксоплазмі в ЗН. Висновок. Застосування нейропротектора при неінфекційному передньому та середньому увеїті призводило до зменшення нейродегенеративних змін в структурах сітківки та зорового нерва.
Ulianov V. Late observation of the neuroprotective effect of citicoline in uveitis: an impact on the ultrastructure of the choriocapillaris, retina and optic nerve in rabbits / V. Ulianov, I. Horianova, N. Molchaniuk // Ukrainian Journal of Ophthalmology. – Odesa : SI «The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine», 2024. – 6(521). – P. 54-59. Режим доступу: https://hdl.handle.net/11300/32375
Keywords: anterior uveitis; intermediate uveitis; non-infectious uveitis model; choroid; acute retinal pigment epitheliitis; optic nerve; citicoline; pathogenesis; передній увеїт; середній увеїт; експериментальна тваринна модель; судинна оболонка; сітківка; зоровий нерв; цитіколін; патогенез